2021
DOI: 10.1371/journal.pone.0247934
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with health-related quality of life in kidney transplant recipients in Korea

Abstract: Health-related quality of life (HRQOL) of kidney transplant recipients is an outcome evaluation after kidney transplants. Therefore, we investigated the associations among perceived health status, social support, self-determination, post-traumatic growth, and kidney transplant recipients’ HRQOL. This study involved a descriptive, self-report survey of 163 kidney transplant recipients visiting an outpatient solid organ transplant center in South Korea. Participants’ general and transplant characteristics, perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 33 publications
1
17
0
2
Order By: Relevance
“…Second, and in contrast, PTG was associated with improved kidney function (30,31), HRQOL (28), and physical activity (33). Recipients of living donor organs, and those with no prior history of organ rejection, had higher average PTGI scores (30,31,34) (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, and in contrast, PTG was associated with improved kidney function (30,31), HRQOL (28), and physical activity (33). Recipients of living donor organs, and those with no prior history of organ rejection, had higher average PTGI scores (30,31,34) (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Higher (better) PTG scores were associated with higher health-related QOL (HRQOL) (r=0.18;p=0.022) (28), and two PTG subscales associated with improved kidney function ( "spiritual change" subscale, C=7.43, p=0.024; "appreciation of life" subscale, C=7.06, p=0.029) (31); PTG positively correlated with autonomous self-regulation (R 2 = 0.08), which itself positively correlated with physical activity, (R 2 = 0.12) (33), while lower (worse) PTG scores were associated with increased rate of graft rejection (OR=0.963;p<0.05) (30). Factors that appeared to either predict or correlate with higher PTG included female sex (F=4.2;p<0.05) (27); greater resilience (ρ=0.403 (LDKT), 0.454 (DDKT); p<0.01) (34), social support (r=0.57;p<0.001) (28), and self-determination (r=0.33;p<0.001) (28); perceived health status (r=0.32;p<0.001) (28); and positive affective tone (ρ=0.22-0.28;p<0.05) (35). Demoralization was associated with lower PTG scores (appreciation of life subscale, p<0.05) (27).…”
Section: Post-traumatic Growthmentioning
confidence: 99%
“…The results of the current study also showed that posttraumatic growth increased as perceived social support and spiritual well-being increased in both the patient and caregiver groups. Studies carried out with different patient groups have found a positive correlation between posttraumatic growth and social support [9,[36][37][38], between posttraumatic growth and spirituality [38]; and between social support and spirituality [9].…”
Section: Characteristics (N) Pgi (X̄ ± Sd) P Mspss (X̄ ± Sd) P Swbs (...mentioning
confidence: 99%
“…No study investigating the effect of spirituality on posttraumatic growth in dialysis patients and their caregivers was found. However, studies conducted with patients who had cancer showed that social support [36]; and spirituality [39]; a study conducted with patients who had myocardial infarction [40] showed that spirituality affected posttraumatic growth.…”
Section: Characteristics (N) Pgi (X̄ ± Sd) P Mspss (X̄ ± Sd) P Swbs (...mentioning
confidence: 99%
“…The literature shows mixed findings regarding whether kidney transplantation is associated with clinically important improvement in HRQOL [19][20][21]. In addition, research findings indicate that HRQOL among kidney transplant recipients (KTRs) is influenced by diverse factors, including perceived health status, mental health, and socioeconomic factors [15,22,23]. Research examining HRQOL among KTRs and hemodialysis (HD) patients in the Middle East is sparse.…”
Section: Introductionmentioning
confidence: 99%